ANALISIS STRATEGI PENCAPAIAN SUSTAINABLE DEVELOPMENT GOALS (SDGs) PADA INDUSTRI KECIL MENENGAH CIK MIA SONGKET - Ade Irma Triani; Muhamad Subhan; Ahmad Syukron Prasaja (CV. Aksara Global Akademia, 2023)
Sustainable Development Goals (SDGs) according to PBB is development that aims to meet the needs of the present without compromising the ability of future generations to meet their own needs. Sustainable development is defined in a broad sense as a country that seeks to achieve sustainable development. However, the strategy for achieving the Sustainable Development Goals in the songket industry, songket entrepreneurs use marketing strategies and innovation strategies which create new innovations to maintain and create sustainable songket product innovations. This study aims to find out how the strategies for achieving the Sustainable Development Goals in the small and medium industry of Cik Mia songket Jambi and the human resource constraints they face. In this study the method used was qualitative by checking the validity of the data using triangulation techniques. The results of the study show that the strategy for achieving the Sustainable Development Goals in the Jambi songket industry can be seen from several aspects, namely that it still has human resource constraints in the weaving sector, therefore it is necessary to optimize the achievement targets in the Sustainable Development Goals.